Criteria of Scientific Truth from Western and Islamic Perspectives - Taupik Hamdani; Syahrul Fadil; Tian Septian; Erni Haryanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Criteria for scientific truth constitute a fundamental aspect of the advancement of knowledge, viewed from both Western and Islamic perspectives. This study examines the differences and similarities regarding these criteria across both perspectives. Generally, the Western approach relies on empirical methods, rationality, and measurable testing, whereas the Islamic perspective incorporates elements of divine revelation and spiritual values ​​as foundations for truth. This research aims to analyze the criteria for scientific truth according to Western and Islamic views and to explore how they can complement each other in the advancement of knowledge. A literature review method was employed, analyzing scholarly works from various sources representing both Western and Islamic paradigms. The findings indicate that, from a Western perspective, scientific truth is grounded in objectivity, falsification, and verification through the scientific method. Conversely, the Islamic perspective holds that scientific truth is not based solely on logic and empirical experience but must also align with divine revelation and Sharia principles. The integration of rationality and spirituality within the Islamic perspective offers a holistic approach to knowledge.